Perceived leadership effectiveness and turnover intention in remote work: The mediating role of communication - Silva, F. A. P.; Velez, M. J. P.; Borrego, P. J. V. B. M. (Caderno Pedagógico, 2024)
In the evolving landscape of remote work, the intersection of leadership communication and employee turnover intention has become a major point of interest for organizational studies. This paper presents a quantitative investigation into how leadership communication is perceived by subordinates in terms of their leaders' effectiveness, and how these perceptions statistically relate to the subordinates' intentions to leave the organization. Judy and d'Amico (1997) predicted that remote work would become a reality in the following decades, with more qualified jobs demanding brains over muscles and physical presence in a specific location becoming irrelevant. Neufeld et al. (2010) explored the impact of leadership perception, also associated with perceived effectiveness, on the communication between managers and subordinates in the remote work environment. The objective of this study was to understand how leadership communication is perceived by employees in terms of direct leaders' effectiveness and how these two factors are statistically related to turnover intention. Turnover intention refers to the individual and voluntary decision to leave an organization (Anwar, 2016). Adopting a quantitative methodology, the study sought to contribute to both the scholarly discourse and practical understanding of remote work practices. In Aprial 2022, a diverse sample of 203 valid respondents was surveyed, inclusive of subordinates across 14 countries and leaders hailing from 30 nationalities. Results revealed a very strong positive correlation (Spearman’s rho = 0.812) between leadership communication and its perceived effectiveness, suggesting that subordinates who regard communication highly also perceive higher leadership effectiveness. However, there's a significant yet weak negative correlation between leadership communication and turnover intentions (Spearman’s rho = -0.343), and similarly, between perceived leadership effectiveness and turnover intentions (Spearman’s rho = -0.299). The study did not find significant evidence of perceived leadership effectiveness mediating the relationship between communication and turnover intentions in remote settings, with a minor indirect effect (Spearman’s rho = -0.0271; p-value = 0.64), comprising about 14% of the total communicative effect on turnover intention. These findings contribute to the literature on remote work dynamics, stressing the importance of effective leadership communication for employee retention. Despite certain study limitations, like sample size and context specificity, the insights provided are valuable for organizational leadership and academia, underscoring communication's vital role in remote workforce management.